The effect of austempering time on mechanical properties of a ductile iron - Baydogˇan, Murat; Çimenogˇlu, Hüseyin (Wiley, 2001)
In this study, the effects of austempering treatment on hardness, tensile properties and wear resistance of a ductile iron were examined. Austempering at 300 °C after austenitising at 900 °C for 100 min improved the mechanical properties of the investigated ductile iron with respect to as‐cast condition. Increase of austempering time from 45 min to 180 min did not cause further improvement in hardness and strength, but increased the ductility and wear resistance, progressively.